Ownership structure, independent chair and firm performance - Mohd. Saat, Nur Ashikin; Kallamu, Basiru Salisu (Universiti Putra Malaysia Press, 2014)
The focus of this study was to examine the effect of ownership structure and the independent board chair as the moderating variable on the performance of companies in the finance industry of the Main Market of Bursa Malaysia. The study used a total of 185 observation data collected from 37 finance companies from the years 2007 to 2011. The results of the study showed that the independent board chair as the moderating variable had a negative relationship with the finance companies' Tobin's Q value. The literature advocates that the independent board chair has an influence on the monitoring of owner managers and in safeguarding minority shareholders' economic interest. On the other hand independent chair control and monitoring of company decisions can be affected by the dominant voice of the CEO, the majority presence of executive directors, the presence of owner manager and leverage.